Penerapan Algoritma K-Means Clustering Dalam Persentase Merokok Pada Penduduk Umur Di Atas 15 Tahun Menurut Provinsi - Rahmat Kurniawan; Suhada Suhada; Rafiqa Dewi (Universitas Budi Darma, 2021)
This research aims to determine the number of people who are smoking the age of 15 years by applying Data Mining. The application uses the K-means algorithm where the data entered is the percentage of smoking. Using this method the data obtained can be grouped into 2 klasters. This research uses secondary data that is obtained from intermediate media that is recorded on the site of the Central Statistics website with the URL address https://www.bps.go.id/. The results gained in this study are grouping the number of smoking percentages that are grouped by as many as 2 klasters is klaster 1 (highest klaster) to get results 22 provinces and klaster 2 (lowest klaster) get 12 provinces.